ORGANIZATION OF THE TRAINING PROCESS OF SHORT DISTANCE RUNNERS AT THE STAGE OF INITIAL SPORTS SPECIALIZATION - Huaxing, Zhu; Zinovenko, K.A.; Vrublevskiy, E.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the main aspects of the organization of the training process of sprint runners in the People’s Republic of China and the Republic of Belarus at the stage of initial sports specialization. Methods and structure of the study. The data of a survey of coaches from Belarus and China who conduct training sessions with young sprinters are presented. Approaches were established for building year-round training of young sprinters, using different means in the structural units of the macrocycle and the main tests that coaches use to assess the preparedness of runners, the time spent on training effects of maximum intensity within the lesson and microcycle, etc. The level of special preparedness of young sprinters aged 12-13 years of the two countries was assessed and the correlation between the experimental characteristics and the sports result in the 100m race was determined. Variants of individual planning of year-round training of young sprinters from the Republic of Belarus and China were subjected to statistical analysis. Results and conclusions. Analysis of the results of the questionnaire survey made it possible to identify both general trends in the implementation of the approach to training young sprinters in the two countries, as well as certain differences. The difference in the level of special preparedness of young sprinters aged 12-13 and the parameters of the main training means in the annual cycle among young runners from Belarus and China is presented. The use by Belarusian coaches of the experience of training athletes in China can be a potential reserve for modernizing the existing system of training sprinters in the country.